Antifungal properties of combined plants extracts against papaya anthracnose - Siqueira Junior, César Luis (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2014)
Fungicides provide the primary means for controlling postharvest fungal decay of fruit and vegetables. Continuous use of fungicides has faced two major obstacles: increasing public concern regarding contamination of perishables with fungicidal residues, and proliferation of resistance in the pathogen populations. Recently, the exploitation of natural products to control decay and prolong storage life of perishables has received more attention. In this work, ethanolic extracts from the bacupari (Rheedia gardneriana Planch) seeds and beach apricot (Labramia bojeri) fruit were investigated for their antifungal activity against fungi Colletotrichum gloeosporioides causal agent of anthracnose disease of papaya fruits. When used alone, the extracts of apricot and bacupari showed no significant inhibitory potential on fungal mycelial growth. When added in a concentration of 10% (v/v) the inhibition obtained were 57% and 43%, respectively. Yet when both extracts were added to the medium at a concentration of 5% (v/v) each, the mycelial growth was completely inhibited. Taken together these results demonstrated the apricot and bacupari potential as a botanical fungicide and an alternative control measure for diseases in papaya plants.